GEODYNAMIC CONDITIONS OF FORMATION AND CLASSIFICATION OF NATURAL OIL AND GAS RESERVOIRS - Yevdoschuk, M.I.; Kryshtal, A.M.; Bondar, H.M. (Institute of Geological Sciences, NAS of Ukraine, 2017)
The compression zone is determined in the geological cross-section of high-catagenesis deep sediments during vertical geodynamic zonation study of horst-anticlinal structures in the Dnieper-Donets Basin. The possibility of forming quazicatagenesis overlays and dilatancy collectors in that cross-section was established as a result of identifying formation conditions of compression zone using published laboratory experiments data of 3-Axis uneven rock samples compression. A number of dilatancy collectors intervals forming with quazi-catagenesis fluid traps the secondary oil and gas reservoirs perspective to find the significant hydrocarbons fields is determined as a result of drilling and classified according to capacitive properties.